School Principal Supervision and Teacher Professionalism: A Study on Leadership in Islamic Schools - Siagian, Nilasari; Amin, Husna; Munawati, Siti; Syafruddin, Syafruddin; Suprihatin, Suprihatin (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
The principal plays a crucial role in improving teachers' professional qualifications, making it essential for an educational institution to have a competent school principal to achieve predetermined goals. This study examines the role of school principals as supervisors in enhancing teacher professionalism in Islamic senior high schools. The research aims to analyze the principal’s role, identify supporting and inhibiting factors in the supervisory process, and assess their impact on teacher professionalism. This study employs a qualitative research method, emphasizing in-depth observation to explore existing phenomena. The research subjects include the school principal and teacher informants. This qualitative study collects data through observation, interviews, and document analysis, with data validity ensured through triangulation. The findings reveal that school principals supervise through planning, implementation, and evaluation while fostering a sense of collegiality. Adequate supervision includes classroom visits, meetings, and individual discussions. The principal employs direct, indirect, and collaborative supervisory approaches. However, time constraints, external principal duties, and hesitancy towards senior teachers hinder the supervisory process. Supporting factors include strong relationships between teachers and principals, the formation of a quality assurance team, and adequate facilities.